NON-VERBAL MEANING OF KERAWANG GAYO BAJU REJE: MULTIMODAL ANALYSIS - Kemas, Wulandari Putri; Sinar, T Silvana; Zein, T Thyrhaya (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2021)
This paper discusses the multimodal analysis of non-verbal meanings in the Kerawang Gayo Reje shirt. It is an ornamental motive made by embroidering cloth. Gayo filigree is the identity of the Gayo. Reje clothes are unique clothes for Reje (king/highest leader) in the village of the Gayonese, and they use several Gayo motives, such as Mata Ni Lao (Matahari), a mandatory motive for a Reje. Each motive contains the meaning of the life of the Gayo tribe. Nowadays, use mandatory clothes on Reje is rarely used. This study aimed to determine the non-verbal meaning of the Kerawang Gayo Reje motives through multimodal analysis. The ethnography method was applied in this study. The data were the Kerawang Gayo Reje shirt's visual art content, the interview result, and observation. The informants were craftsman/tailor; and the Majelis Adat Gayo leaders (Gayo traditional centre) in Central Aceh. The data were analyzed by explaining the meaning lies in the means of communication and each meaning centrally, and dominantly of Kerawang Gayo Reje shirt The result of the study showed that there are four types of motives on Reje's clothes, Mata Ni Lao, Tali Puter Tige, Tekukur, and Tapak Sleman. On the Reje shirt, there is only one colour used, which is yellow. The meaning is justice and prosperity for the Gayo tribe community. It is hoped that a Reje will be fair to the people and provide prosperity for the Gayo tribe community.